The Effect of Raising School Quality on Earnings - Harry Anthony Patrinos; George Psacharopoulos (Global Labor Organization (GLO), 2025)
The evidence underscores the need to shift attention from school attainment to actual learning. While the average global return to an additional year of schooling is about 10 percent, a one standard deviation increase in test scores raises earnings by 15 percent. Studies show that including direct measures of skills reduces the estimated return to schooling, revealing the stronger role of quality. These findings suggest that education policy should prioritize learning outcomes, not just years in school, to more accurately reflect the economic value of education.
Keywords: I21; I26; J24; 330; Returns to education; cognitive skills; earnings